Development of an axial flow ventricular assist device using computational fluid dynamics and particle image velocimetry measurement - Su, Boyang (2011)
Due to the limited heart donors available, there are many people with end-stage heart disease who die every year. Ventricular Assist Devices (VADs) are thus, developed to maximize the survival and minimize the morbidity of these patients. Axial flow VADs have gained tremendous interests due to its smaller size and favorable anatomical fit. In the development of an axial flow VAD, besides the hydraulic performance, hemolysis and thrombosis are important parameters closely related to the internal flow conditions to be considered. Therefore, the present study focuses on the hemodynamics of the axial flow VAD using Computational Fluid Dynamics (CFD) which allowed the VAD model to be further optimized based on the simulation results. These simulation results were validated later using Particle Image Velocimetry (PIV) measurements.